LEGAL PROTECTION FOR CREDITORS WHOSE CLAIMS ARE REJECTED IN THE POSTPONEMENT OF DEBT PAYMENT OBLIGATIONS - Prabowo, Megawati; Purnawan, Amin (Jurnal Hukum Khaira Ummah, 2024)
This thesis aims to analyze the legal protection for creditors whose claims are rejected in the Debt Payment Suspension (PKPU) process based on Law Number 37 of 2004 concerning Bankruptcy and Debt Payment Suspension (UUK-PKPU) and identify the weaknesses that arise in this protection. This study uses a normative legal method with a descriptive analytical approach, by analyzing laws and regulations, court decisions, and related legal literature. Based on the study, it is concluded that legal protection for creditors whose claims are rejected in the PKPU process is still very limited. UUK-PKPU does not provide a renvoi mechanism as in bankruptcy, so creditors cannot file a separate lawsuit with the commercial court. In addition, there are several weaknesses in UUK-PKPU and its implementation, including: lack of clarity and detail in the rules for verifying claims; lack of transparency and access to information for creditors; limited time for verifying claims; and limited forums for legal remedies for creditors whose claims are rejected.